Uji Marshall Immersion Pada Campuran AC-WC Menggunakan Rechlamed Asphalt Pavement (RAP) - Tommy Iduwin; Dicki Dian Purnama; Ranti Hidayawanti (FORUM MEKANIKA, 2020)
Using replacement materials in recent years is often used in research activities and also in construction activities. Reclaimed Asphalt Pavement (RAP) is an alternative material for use as a pavement material because it reduces the use of natural aggregates and new asphalt binders, which are needed to make asphalt mixtures. This research used a variation of RAP 0%, 25% and 35%. The test in reasearch is the Marshall test to determine the value of the optimum asphalt content and Marshall immersion. The mold of the test object used was a 3 x 4 inch cylinder with a total of 54 specimens. The results of the material characteristics test feel the 2018 highways specification standards. For the value of the Optimal Asphalt Content obtained for each variation is 5.4% for Rap 0%, 5.6 for Rap 25% and 6% for RAP 35%. In the marshall immersion test, the stability value of the remaining marshall after 24 hours of immersion was 91.4% for)% RAP, 90.7% for RAP 25% and 90.1% for RAP 35%. Keywords: AC-WC, RAP, Optimal Asphalt Content, Marshall Immersion